Pin number theft recognition and cash transaction using sixth sense technology in ATM/CDM - Pradeep Kumar, S; Shanmugasundaram, N (International Journal of Engineering and Technology, 2018)
Nowadays peoples using credit/debit card for cash transaction for their daily needs. Meanwhile for deposit and withdrawal of huge amount the consumers use the automated teller machine or cash deposit machine. Due to this the crime related to ATM like pin number theft, fraud calls etc increasing day by day. This paper aim to reduce the risk related to pin number theft. We proposed a sixth sense technology which can access by our gestural interface to do the normal operation for cash transaction rather than touching the pin number plate which will be helpful for eliminating the theft related with pin number tracking. The experimental prototype model is designed and the results are verified and presented in this paper.Â